Effect of Cross-Sectional Designs of Different Ni-Ti Files on Shaping Ability After Repeated Usage in Simulated Root Canals. - Fikrat Shawqi Qaddori; Raid Fahim Salman (Erbil Dental Journal, 2024)
Background and Objective: The study aimed was to compare the effect of cross-sectional designs of five rotary systems (One Curve, 2Shape, K3-i File, E3 Azure, Neolix), on the shaping ability of the files in simulated resin blocks under controlled conditions with five repeated use. The shaping ability of the files includes the following variables: (1) Longitudinal sectional area difference, (2) Canal wall surface area difference, (3) Canal volume difference, (4) SMI (structure material index) difference, (5) Cross-sectional area difference.